(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2020)
Based on the characteristics of the translation of comics in general, in this article we have focused our research on one of the globally known comics. Considering the translation of comics as a translation branch par excellence, since the translator must transmit the message of a concise discourse – sometimes diverse and complex and always related to the corresponding image – into another language and in a limited space, the article is about the importance of the cultural context in this type of translation, based on the analysis of ten stories of Asterix taking place in various territories: Hispania, Belgium, Rome, Brittany, Helvecia... Considering that all the René Goscinny and Albert Uderzo’s episodes have been translated into both Spanish and Serbian, we have made a comparative analysis of procedures, approaches and solutions that the translators Víctor Mora and Đorđe Dimitrijević have applied in their respective translations, exploring verbal games, linguistic particularities, humor, phrases made and colloquial expressions. The objective of this research is to verify the difference between the translation of the comic discourse to a Romance language (Spanish) and a Slavic language (Serbian), as well as to explore contextual nuances, intertextualities and stereotypes, in order to find out how these elements have been transmitted or lost during the translation procedure. Therefore, we have concluded that the fact that one language is Romance and another Slavic is not crucial and does not influence the understanding of the speech, but it does contain different nuances due to translators’ abilities. Keywords: comic translation, cultural context, Asterix in Spanish, Asterix in Serbian, humor.